2016
DOI: 10.13168/agg.2016.0014
|View full text |Cite
|
Sign up to set email alerts
|

The impact of deep underground coal mining on Earth fissure occurrence

Abstract: Deep underground mining commonly causes land subsidence and mining tremors. The occurrence of Earth fissures induced by deep underground mining operations is a rare phenomenon. The development of Earth fissures is a rapid and unexpected process causing a particular hazard to the developed areas. The presented research focuses on the investigation of Earth fissure propagation in the light of geotechnical and geological condition. The presented approach can be used for establishing most significant risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…In some papers, attention has been paid to a certain threshold value of horizontal strain caused by the underground exploitation of deposits. It has been reported [9,18,19] that linear discontinuous deformations have been observed when the horizontal tensile strain has exceeded the value of 9 mm/m. Following these findings, the same value of threshold strain was thus determined for two Polish mining regions [9,18] and a Chinese basin [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some papers, attention has been paid to a certain threshold value of horizontal strain caused by the underground exploitation of deposits. It has been reported [9,18,19] that linear discontinuous deformations have been observed when the horizontal tensile strain has exceeded the value of 9 mm/m. Following these findings, the same value of threshold strain was thus determined for two Polish mining regions [9,18] and a Chinese basin [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported [9,18,19] that linear discontinuous deformations have been observed when the horizontal tensile strain has exceeded the value of 9 mm/m. Following these findings, the same value of threshold strain was thus determined for two Polish mining regions [9,18] and a Chinese basin [19]. In his paper [5], Kowalski noted that primary discontinuous deformations are formed at values of horizontal tensile strain exceeding 9 mm/m, whereas secondary deformations can occur even when these values grow by ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation withers and dies when soil moisture is lost through these ground fissures, such that the surrounding ecosystems are changed irreversibly (Dagvadorj, Byamba, and Ishikawa, 2018). Ground fissures also compromise the safety of underground mining activities, especially when these fissures extend downwards and connect with the fracture zone of strata, resulting in gas leakages, outbursts of water and sand, and other accidents (Hu, Wand, and He, 2014;Malinowska and Hejmanowski, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, although studies have shown that there is a linear relationship between the width of the ground fissure during development and the horizontal deformation of the surface, the factors that control the formation of the ground fissure are still not clear. Third, because dynamic fissures can self-heal (Malinowska and Hejmanowski, 2016), researchers have proposed that fissures should be remediated once the surface has stabilized after subsidence. However, engineers have found that the depth to which ground fissures and rock fractures penetrate influences the safety of the mining operations, especially in shallow coal seam mines.…”
Section: Introductionmentioning
confidence: 99%